PB5 Establishment of a provincial data repository to facilitate reporting performance measurements for Alberta Emergency Departments. (19th March 2012) - Holroyd, B; Bullard, M; Lang, E; Liss, K; Schmid, C; Heintz, L; Thiessen, L; Lighter, D; Rowe, B
Abstract : Objectives and Background: The ability to accurately define and measure Emergency Department (ED) patient utilisation and flow parameters, as well as metrics related to patient safety and quality of care are essential to the operations and accountability of emergency patient care delivery. Alberta Health Services (AHS) is responsible for the delivery of health services to 3.7 million people in Alberta (AB), Canada, with total provincial ED visits exceeding 1.9 million/year. The Data Integration, Measurement and Reporting Department of AHS, in collaboration with emergency clinical leadership, has undertaken the development for the AHS Data Repository for Reporting (AHSDRR). This database will provide unique functionality. It can be interrogated by a wide range of stakeholders to yield quality and performance indicator reports with a variety of adjustable filtering parameters, such as patient demographics, institution and region. Methods: The AHSDRR architecture integrates clinical and administrative data from multiple sources. Data sources will include 11 urban teaching EDs, one freestanding ED, two Urgent Care centers, and four regional EDs utilising ED Information Systems. A comprehensive standardised ED data set from chart abstraction will be included in the AHSDRR for all provincial EDs. ED patient experience survey data and vital statistics data will be incorporated. Results: With successful development and testing, AHSDRR Emergency Release 1 became operational on September 15th, 2011. Conclusions: The AHSDRR represents an innovative opportunity to employ multiple data resources to describe emergency care delivery in Alberta. This system will facilitate standardised reporting of ED performance and quality information in formats compliant with national and international standards. With additional clinical information sources, AHSDRR future applications have considerable growth potential.